1989
DOI: 10.3189/s0022143000004512
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Variations in Strain and Surface Tilt on Storglaciären, Kebnekaise, Northern Sweden

Abstract: ABSTRACT. Tiltmeters that can detect changes in slope of a glacier surface as small as 0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 20 publications
(26 reference statements)
4
26
0
Order By: Relevance
“…Consequently, the region of high subglacial water pressures and accelerated ice motion took time to propagate downstream (Gudmundsson, 2002;Vieli and others, 2004). The region moved downstream with a velocity of 50-100 m h À 1 , which is similar to values observed on other alpine glaciers (Iken and Bindschadler, 1986;Jansson and Hooke, 1989;Gudmundsson, 2002) and our inferred value during rain events.…”
Section: Diurnal Melt Cyclessupporting
confidence: 89%
See 1 more Smart Citation
“…Consequently, the region of high subglacial water pressures and accelerated ice motion took time to propagate downstream (Gudmundsson, 2002;Vieli and others, 2004). The region moved downstream with a velocity of 50-100 m h À 1 , which is similar to values observed on other alpine glaciers (Iken and Bindschadler, 1986;Jansson and Hooke, 1989;Gudmundsson, 2002) and our inferred value during rain events.…”
Section: Diurnal Melt Cyclessupporting
confidence: 89%
“…This propagation speed is similar to values observed at other glaciers (Iken and Bindschadler, 1986;Jansson and Hooke, 1989;Gudmundsson, 2002). A high-pressure zone propagating downstream suggests that our stations at higher elevations (G05-G06) will have returned to normal ice flow �10 hours before our stations at lower elevations (G01-G04).…”
Section: Rain Eventssupporting
confidence: 85%
“…We suggest, however, that up‐basin dipping beds may provide an alternative mechanism for forming glacial steps without the factors previously studied and that up‐basin dipping beds may contribute to the formation of glacial steps in the presence of the factors mentioned above. We find tentative support for these assertions in the observations of Jansson and Hooke () at Storglaciären, Sweden where the downstream ends of two overdeepenings are formed in up‐glacier dipping rock layers, indicating geometry similar to that depicted in Fig. .…”
Section: Discussionsupporting
confidence: 80%
“…Similar events, referred to as a mini-surge from observations on Variegated Glacier (Humphrey et al, 1986), have also been observed elsewhere, e.g. on Storglaciären (Jansson and Hooke, 1989) and on Black Rapids and Fels Glaciers (Raymond et al, 1995). Iken et al (1996) performed slug tests in bore holes on Gornergletscher, Switzerland, and yielded results indicating storage changes in cavities and channels beneath the glacier.…”
Section: Subglacial Storagementioning
confidence: 91%